2010
DOI: 10.1590/s0100-204x2010001000001
|View full text |Cite
|
Sign up to set email alerts
|

Leaf development and growth of selected sugarcane clones in a subtropical environment

Abstract: -The objective of this work was to compare phyllochron and leaf area on individual stalks of selected sugarcane (Saccharum officinarum) clones grown in a subtropical environment. A two-year field experiment was carried out in Santa Maria, RS, Brazil, during the 2007/2008 and 2008 growing seasons. Three sugarcane clones were used: IAC 822045 (early), SP 711406 (median) and CB 4176 (late), in a complete randomized block design, with four replications. Expanded leaf and total leaf (tips) number were determined, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
7
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
1
7
0
5
Order By: Relevance
“…International Journal of Agronomy Therefore, leaf area development and growth are critical in determining the canopy leaf area index (LAI) to maximize the interception of solar radiation by the crop canopy for photosynthesis, leading to the accumulation of biomass [7], which finally defines crop yield [8]. Hence, slow or inefficient development of the plant canopy may be critical in limiting the final yield produced by a sugarcane crop [9].…”
mentioning
confidence: 99%
“…International Journal of Agronomy Therefore, leaf area development and growth are critical in determining the canopy leaf area index (LAI) to maximize the interception of solar radiation by the crop canopy for photosynthesis, leading to the accumulation of biomass [7], which finally defines crop yield [8]. Hence, slow or inefficient development of the plant canopy may be critical in limiting the final yield produced by a sugarcane crop [9].…”
mentioning
confidence: 99%
“…In both CWs, the sugarcane foliar area increased significantly during the first six months of growth, reaching 6000 cm 2 /plant and 5000 cm 2 /plant, respectively, for CW T1 and CW T3, and tended towards stabilization in the remaining growth period. For the same species and on a subtropical climate, Streck et al [21] report a value of sugarcane foliar area of 4000 cm 2 /plant four months after planting. Robertson et al [22] reported about 5000 cm 2 /plant five months after planting, under high input conditions in a tropical climate.…”
Section: Sugarcane Growth Indicatorsmentioning
confidence: 99%
“…Klon-klon yang diuji ditumbuhkan dalam lingkungan tumbuh yang homogen sehingga perbedaan kandungan khlorofil daun dipengaruhi oleh genetik tanaman. Streck et al (2010) menyebutkan kandungan khlorofil dalam daun dipengaruhi oleh genetik tanaman, kondisi lingkungan tumbuh, dan interaksi dari keduanya. Demikian pula Zhao et al (2015) menyebutkan kandungan khlorofil daun hanya dipengaruhi oleh genetik tanaman bila kondisi lingkungan tumbuhnya homogen.…”
Section: Hasil Dan Pembahasanunclassified
“…Analisis regresi linier berganda panjang ruas terhadap jumlah ruas dan Fv/Fm diperoleh nilai pengaruh (koefisien korelasi) sebesar 77.2% dengan jumlah ruas berkorelasi negatif dan Fv/Fm berkorelasi positif. Klon/varietas yang mempunyai jumlah ruas yang sedikit dan nilai Fv/Fm yang tinggi akan menghasilkan panjang ruas yang lebih panjang(Streck et al, 2010). Hasil penelitianJunejo et al (2010),Patel et al (2014) danGomathi et al (2013) memperlihatkan perbedaan panjang ruas tebu akibat perbedaan varietas yang digunakan.Empat klon (17, 87, 104, dan 212) berpanjang batang tidak berbeda dan 8 klon lainnya lebih pendek dibanding varietas Cenning.…”
unclassified
See 1 more Smart Citation